Palestinian Child Institute - Masa AlRefae; Ola Saadeh (My University, 2023)
The project revolves around the development of a comprehensive application designed to allow children with neurological disorders, through their families, to follow up with a doctor for treatment. The project delivers tangible benefits to both specialists and parents. The application enables the specialist to communicate with the family of the child undergoing treatment in a smooth and flexible manner, take appointment bookings for treatment without the need to go to the institute, submit homework assignments in an organized manner, organize the delivery of reports, arrange them, and save them from loss. Many functionalities are provided through the app: • User Registration: Users can create standard user accounts by providing personal information, including their name, profile picture, and location. • Instant Messaging System: Parents can engage in immediate and efficient communication with the current specialist responsible for their child's treatment, which may involve one or more specialists and the parents can communicate with each other through the chat feature. • Notification System: The application sends notifications to parents regarding their booked appointments , to do list , if there is an exercise added , if there an valid appointments added , if there is announcement from specialist. • Appointment Scheduling: Allowing parents to booking an appointment and view their bookings. • Exercise Customization: The platform offers students specialized exercises aligned with the available clinics. Each exercise is designed to enhance specific cognitive functions, such as memory, intelligence, and speech. This tailored approach ensures that students engage in targeted activities that contribute to their overall cognitive development, and there is feedback to Specialist about children behavior in Exercise by using AI and ML tools. • Report Requests: Parents can access all reports and test results, or request evaluations after each session. In cases where a specialist delays providing a report, parents can initiate a request for the report through the application. 10